Meningkatkan Potensi Desa melalui pemanfaatan Website Desa Sebagai Wujud Ekonomi Kreatif Desa Genengan Kecamatan Doko Kabupaten Blitar - Miftakhul Rohman; Moch Bayu Fadilah; Eka; Gabrielle; Divina Dea Rudita; Adzinat Robbi Malik; Moch Ma'ruf Iskandar (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2023)
This work program aims to increase village potential through the use of websites as a form of creative economy in Genengan Village. The development model used is a prototype model which consists of analysis, design and implementation stages. Data collection was carried out by conducting observations and interviews. The data collected is in the form of interviews. The results of this work program show that a village website is very necessary as a source of information to improve the creative economy in Genengan Village.